Respuesta :

Answer:

[tex] - \frac{19}{18} = - 1.05 = - 1 \frac{1}{18} [/tex]

Step-by-step explanation:

[tex] \frac{ - \frac{4}{5} }{ \frac{9}{10} } - \frac{1}{6} \\ \\ ( - \frac{4}{5} \div \frac{9}{10} ) - \frac{1}{6} \\ \\ ( - \frac{4}{5} \times \frac{10}{9} ) - \frac{1}{6} \\ \\ ( - \frac{4}{1} \times \frac{2}{9} ) - \frac{1}{6} \\ \\ ( - \frac{8}{9} ) - \frac{1}{6} \\ \\ - \frac{16}{18} - \frac{3}{18} = \frac{ - 19}{18} = - 1.05 = - 1 \frac{1}{18} [/tex]

I hope I helped you^_^

[tex]\large\color{pink}{\mid{\fbox{\bf{given\: expression}}\mid}}[/tex]

‎ ‎‎‎ ‎ ‎‎‎ ‎ ‎‎‎ ‎ ‎‎‎ ‎ ‎‎‎ ‎ ‎‎‎ ‎ ‎‎‎ ‎ ‎[tex]\huge\bf{= \frac{ \frac{ - 4}{5} }{ \frac{9}{10} } - \frac{1}{6}} [/tex]

[tex]\large\bf{\underline{We\:can \:solve \:it\:as:-}}[/tex]

‎ ‎‎‎ ‎ ‎‎‎ ‎ ‎‎‎ ‎ ‎‎‎ ‎ ‎‎‎ ‎ ‎‎‎ ‎ ‎‎‎ ‎ ‎[tex]\large{= (\frac{ \frac{ - 4}{5} }{ \frac{9}{10} } ) - \frac{1}{6}} [/tex]

‎ ‎‎‎ ‎ ‎‎‎ ‎ ‎‎‎ ‎ ‎‎‎ ‎ ‎‎‎ ‎ ‎‎‎ ‎ ‎‎‎ ‎ ‎[tex]\large{=( \frac{ - 4}{5} \times \frac{10}{9} ) - \frac{1}{6}} [/tex]

‎ ‎‎‎ ‎ ‎‎‎ ‎ ‎‎‎ ‎ ‎‎‎ ‎ ‎‎‎ ‎ ‎‎‎ ‎ ‎‎‎ ‎ ‎[tex]\large{=\frac{ - 8}{9} - \frac{1}{6}}[/tex]

[tex]\large\bf{\underline{Taking \:LCM}}[/tex]

‎ ‎‎‎ ‎ ‎‎‎ ‎ ‎‎‎ ‎ ‎‎‎ ‎ ‎‎‎ ‎ ‎‎‎ ‎ ‎‎‎ ‎ ‎[tex]\large{= \frac{( - 8 \times 2) - (1 \times 3)}{18}} [/tex]

‎ ‎‎‎ ‎ ‎‎‎ ‎ ‎‎‎ ‎ ‎‎‎ ‎ ‎‎‎ ‎ ‎‎‎ ‎ ‎‎‎ ‎ ‎[tex]\large{= \frac{ - 16 - 3}{18}} [/tex]

‎ ‎‎‎ ‎ ‎‎‎ ‎ ‎‎‎ ‎ ‎‎‎ ‎ ‎‎‎ ‎ ‎‎‎ ‎ ‎‎‎ ‎ ‎[tex]\large{=\frac{ - 19}{18}} [/tex]

______________________________________

[tex]\huge\bf\pink{⟹-\frac{ 19}{18}}[/tex]

Otras preguntas

ACCESS MORE